2016
DOI: 10.14411/eje.2016.065
|View full text |Cite
|
Sign up to set email alerts
|

Settling moths as potential pollinators of Uncaria rhynchophylla (Rubiaceae)

Abstract: Abstract. Nocturnal pollinators such as moths have received less attention than diurnal insects. To elucidate whether nocturnal moths are important pollinators, we observed both the diurnal and nocturnal visitors to the fl owers of Uncaria rhynchophylla (Rubiaceae) in a warm-temperate forest in central Japan. The diurnal visitors included various taxonomic groups (e.g., bees, hoverfl ies and butterfl ies). The nocturnal visitors were exclusively moths (Geometridae, Erebidae, Noctuidae and Crambidae). Pollen gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Settling moth pollination has been reported for flowers of species of Apocynaceae (e.g., Hoya (Mochizuki et al 2017), Marsdenia (Sakagami et al 2019), and Vincetoxicum (Yamashiro et al 2008;Nakahama et al 2013)), Campanulaceae (e.g., Adenophora Funamoto & Ohashi 2017;Funamoto 2019)), Caprifoliaceae (e.g., Lonicera (Xuan et al 2015)), Lecythidaceae (e.g., Barringtonia )), Orchidaceae (e.g., Platanthera (Inoue 1983; and Habenaria (Xiong et al 2019)), Thymelaeaceae (e.g., Aquilaria (Chen et al 2016), Diplomorpha (Fig. 1G; Okamoto et al 2008), and Stellera (Zhang et al 2011b)), and Rubiaceae (e.g., Uncaria (Funamoto & Sugiura 2016)). Several species of pyralid and crambid moths visit flowers of Balanophora species, and these moths oviposit their eggs on the flowers, after which the larvae of the moths consume the floral tissues (Kawakita & Kato 2002).…”
Section: Settling Mothsmentioning
confidence: 99%
“…Settling moth pollination has been reported for flowers of species of Apocynaceae (e.g., Hoya (Mochizuki et al 2017), Marsdenia (Sakagami et al 2019), and Vincetoxicum (Yamashiro et al 2008;Nakahama et al 2013)), Campanulaceae (e.g., Adenophora Funamoto & Ohashi 2017;Funamoto 2019)), Caprifoliaceae (e.g., Lonicera (Xuan et al 2015)), Lecythidaceae (e.g., Barringtonia )), Orchidaceae (e.g., Platanthera (Inoue 1983; and Habenaria (Xiong et al 2019)), Thymelaeaceae (e.g., Aquilaria (Chen et al 2016), Diplomorpha (Fig. 1G; Okamoto et al 2008), and Stellera (Zhang et al 2011b)), and Rubiaceae (e.g., Uncaria (Funamoto & Sugiura 2016)). Several species of pyralid and crambid moths visit flowers of Balanophora species, and these moths oviposit their eggs on the flowers, after which the larvae of the moths consume the floral tissues (Kawakita & Kato 2002).…”
Section: Settling Mothsmentioning
confidence: 99%
“…Visitors to the S. praecox flowers were randomly sampled using an insect net, and the proboscis lengths of the flower visitors were measured to the nearest 0.1 mm, with the aid of a slide caliper or with an ocular micrometer, under a stereomicroscope in the laboratory. The number of pollen grains of S. praecox on each flower visitor was counted using a stereomicroscope and categorized as 0, 1–10, 11–100 and > 100, in accordance with previous investigations (Funamoto & Sugiura, 2016). Fisher's exact test was used to make comparisons between the diurnal flower visitors and the nocturnal settling moths (all collected from the female flowers) regarding the proportions of insects with S. praecox pollen grains.…”
Section: Methodsmentioning
confidence: 98%
“…generalists (Devoto et al, 2011;Macgregor et al, 2019) and could be complimentary to diurnal pollinators (Oliveira et al 2004, Devoto et al 2011, Willmer 2011). In addition, moths might be more effective than diurnal pollinators (Miyake & Yahara 1998, Groman & Pellmyr 1999, Funamoto & Sugiura 2016) despite lower visitation rates and make a considerable contribution to large scale outcrossing as they potentially move pollen longer distances than diurnal pollinators (Herrera 1987, Miyake & Yahara 1998, Young 2002. While a substantial number of individuals or species might carry high pollen loads, most pollen movement is dominated by a small subset of species (Devoto et al 2011, Banza et al 2015, Macgregor et al 2017.…”
Section: Approach 2: Examine All Moths Captured In An Ecosystem For Pollenmentioning
confidence: 99%
“…and two species of evening primrose (Oenothera spp.). This approach is widely used (Oliveira et al 2004, Huber et al 2005, Makholela & Manning 2006, Atwater 2013, Benning 2015, Funamoto & Sugiura 2016, Peter & Venter 2017, and many of these studies reported new relationships between flower-visiting moths and plant species. We have employed this approach This article is protected by copyright.…”
Section: Approach 3: Monitor Only Flowers Thought To Be Moth Pollinatedmentioning
confidence: 99%
See 1 more Smart Citation